Reliability and Validity of Nurses' Experiences of Infection Prevention and Control Questionnaire - ÇÖVENER ÖZÇELİK, ÇAĞRI (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Nosocomial infections are the primary reason of morbidity and mortality especially at children's hospitals. Thus, educating pediatric health care providers is rather crucial in order to protect children from exposure to infection. This study was planned to examine reliability and validity of Nurses' Infection Prevention and Control Observation Questionnaire in Turkish Language. Methods: This methodological study was carried out at a randomly selected Children's Hospital from each of the 7 regions of Turkey. In total, 443 pediatric nurses from those hospitals participated in the study. Content validity, construct validity, inter-consistency reliability and item total correlation of the questionnaire were analysed in order to adjust reliability and validity. Results: The questionnaire has good content, face and construct validity. The acceptable level for scales' items was above 0.30 and had one factor according to results of explanatory factor analysis. The questionnaire model fitted the data according to confirmatory factor analysis. A level of Cronbach's alpha at 0.74 was considered to be an acceptable level of reliability and item-total score correlation of the study-except for four items - was identified above 0.30. Conclusion: The questionnaire was determined as a reliable and validate tool in evaluation of observation for nurses' infection prevention and control.
Keywords: Infection control; pediatric nurse; validity; reliability